The Effect of Health Belief Model on Prevention Chronic Desease DM in Elderly at Bangun Rejo Village Tanjung Morawa District in 2022 - Rosmega Pakpahan; Zulkarnain Batubara; Petra Dian Sari Zega; Siti Nurfadhilah (Science Midwifery, 2022)
This study aims to determine the effect of The Health Belief Model in the prevention of chronic disease Diabetes Mellitus in the elderly . This research was conducted in Bangun Rejo Village, Tanjung Morawa sub-district, Deli Serdang Regency. This study used a quasi-experimental design with a non-equivalent control group research design. The number of samples in this study were 34 people who were taken using a purposive sampling technique by taking into account the inclusion criteria. The sample was divided into 17 people as the experimental group and 17 people as the control group. The measuring instruments used in this study were questionnaires that had been tested for validity and reliability, blood glucose measuring devices, and observation sheets. The experimental group was given an intervention. Effect of The Health Belief Model on the prevention of chronic disease and in the elderly. The analysis used was univariate analysis and bivariate analysis with dependent and independent t tests. The results showed that before being given health education, the influence of The Health Belief Model was that the majority of respondents had sufficient knowledge as many as 9 people (38.2%) and after being given health education based on The Health Belief Model had good chronic disease prevention as many as 17 people (50, 0%). Statistical results obtained p value (0.000) < (0.05), so that the results obtained that there is an effect of The Health Belief Model in the prevention of chronic diseases in the elderly. The results of this study are expected to be one of the nursing interventions in increasing the prevention of chronic diseases in the elderly.